Time traders: Derivatives, Minsky and a reinterpretation of the causes of the 2008 Global Financial Crisis. Issue 3 (3rd July 2019) - Troncoso, Joshua N.
Abstract: There are two major competing theoretical explanations of the 2008 Global Financial Crisis: neoclassicism and pos Keynesianism. Neoclassicists assume that crises are exogenous and are thus concerned with assessing the proper regulation and enforcement regime. Central to the post Keynesian position is Hyman Minsky, whose financial instability hypothesis holds that crises are due to the structure of financial assets in complex economies and are thus endogenous. This article uses qualitative financial data to show how derivatives and other exotic instruments (neoclassical analyses) bypassed the deflationary safety valve in Minsky's financial instability hypothesis. In his model, uncertainty and risk valuations either push demand prices for financial assets below what banks are willing to sell or greater risk valuations will push the costs of producing assets above what the market will pay; initiating a deflationary break. Derivatives broke this mechanism. Lenders in the 2000s used complex financial instruments to artificially eliminate risk, which made the supply-price of financial assets inelastic to upward shifts in uncertainty. Without supply-side risk to push prices above the demand curve, lenders bypassed the mechanism responsible for popping speculative bubbles and initiating deflationary market corrections. Thus, Minsky's ponzi phase was more difficult to stop than his model would have predicted.